Fifty shades of black: When negative emotions enhance the relationship between the dark triad and knowledge sabotage - Silva, D.; Junça-Silva, A.; Pinheiro, P. G.; Sucena, A. (International Journal of Organizational Analysis, 2025)
Purpose Relying on the trait activation theory, this study aims to develop a framework that explains when the three dimensions of the dark triad (Machiavellianism, psychopathy and narcissism) influence knowledge sabotage (KS) in the higher education environment, by conceiving negative affect as a moderator in this relationship. Design/methodology/approach To test the hypotheses, the authors collected data from 221 individuals using a self-administered questionnaire. Findings The results showed that (1) there is a positive relationship between Machiavellianism, psychopathy, narcissism and KS, and that (2) negative affect moderated these relationships in such a way that the relations became stronger when negative affect was higher (when compared to lower levels of negative affect). Research limitations/implications Despite its contribution to the literature, this paper contains limitations. The sample size (n = 221) is relatively small and may not be representative of the population. Another limitation is related to the very nature of the questionnaire survey. Given the sensitivity of the questions and despite the guaranteed anonymity, there may be a voluntary and/or involuntary tendency to answer within socially acceptable matrices. Practical implications This study highlights key implications for higher education policymakers to mitigate KS behaviours and enhance knowledge sharing. Originality/value The novelty of this paper is that it analyses the relationship between dark triad traits and KS in the higher education institutes environment and the moderating role of negative emotions in this relationship.